It’s all in your head – how anticipating evaluation affects the processing of emotional trait adjectives - Schindler, Sebastian; Wegrzyn, Martin; Steppacher, Inga; Kissler, Johanna (Frontiers in Psychology, 2014)
Language has an intrinsically evaluative and communicative function. Words can serve to describe emotional traits and states in others and communicate evaluations. Using electroencephalography (EEG), we investigate how the cerebral processing of emotional trait adjectives is modulated by their perceived communicative sender in anticipation of an evaluation. 16 students were videotaped while they described themselves. They were told that a stranger would evaluate their personality based on this recording by endorsing trait adjectives. In a control condition a computer program supposedly randomly selected the adjectives. Actually, both conditions were random. A larger parietal N1 was found for adjectives in the supposedly human-generated condition. This indicates that more visual attention is allocated to the presented adjectives when putatively interacting with a human. Between 400 and 700ms a fronto-central main effect of emotion was found. Positive, and in tendency also negative adjectives, led to a larger late positive potential (LPP) compared to neutral adjectives. A centro-parietal interaction in the LPP-window was due to larger LPP amplitudes for negative compared to neutral adjectives within the ‘human sender’ condition. Larger LPP amplitudes are related to stimulus elaboration and memory consolidation. Participants responded more to emotional content particularly when presented in a meaningful ‘human’ context. This was first observed in the early posterior negativity window (EPN, 210-260 ms). But the significant interaction between sender and emotion reached only trend-level on post-hoc tests. Our results specify differential effects of even implied communicative partners on emotional language processing. They show that anticipating evaluation by a communicative partner alone is sufficient to increase the relevance of particularly emotional adjectives, given a seemingly realistic interactive setting.